Peningkatan Kompetensi Guru melalui Coaching for Teaching di Al Baitul Amien - Hakim, Miftahul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Coaching for Teaching is a strategic approach to teacher professional development, emphasizing reflective practice, empathy, and student empowerment. This community engagement initiative aimed to enhance teachers’ understanding, motivation, and skills in applying coaching principles to classroom instruction. The program was conducted at SMP Al Baitul Amien over 8 hours and involved 30 teacher participants. The training used lectures, simulations, and case studies. Evaluation was carried out using a Likert-scale questionnaire and open-ended questions. The results showed significant improvements in understanding of coaching principles (from 2.4 to 4.3), motivation to apply coaching (from 2.9 to 4.5), and coaching skills (from 2.2 to 4.0). Qualitative responses revealed that teachers gained deeper awareness of meaningful classroom relationships. The training proved effective as a teacher development model and is recommended for replication and further development through school-based learning communities.